Factors influencing academics’ knowledge sharing behaviour in United Arab Emirates public universities - Skaik, Huda; Othman, Roslina (2013)
The main objectives of this research are to (i) explore the relationship between types of knowledge and academics’ knowledge sharing behaviour, (ii) examine the relationship between knowledge sharing behaviour and its predictors based on the Theory of Planned Behaviour, and (iii) identify the factors motivating and hindering academics’ knowledge sharing behaviour. Adopting Ajzen’s Amended Theory of Planned Behaviour, this research used the quantitative research approach employing an online survey using questionnaire to collect data from academics in ten public universities. Data were analyzed using SPSS and PLS-SEM. The analysis process involved assessment of the measurement model to evaluate the items reliability and validity, and assessment of the structural model to evaluate its validity, path coefficients, and test the hypotheses. The results revealed a high level of knowledge sharing practice. Furthermore, the results showed that academics’ knowledge sharing behaviour is significantly influenced by explicit knowledge, tacit knowledge, and intention. Intention itself is significantly influenced by attitude, subjective norms, selfefficacy, but not influenced by controllability. Also, attitude is significantly and positively influenced by trust and reputation as motivators of knowledge sharing behaviour. Whereas, controllability is significantly and negatively influenced by lack of time and poor communication as barriers of knowledge sharing behaviour. Keywords - academics, knowledge sharing behaviour, Theory of Planned Behavior, UAE, universities.